2012
DOI: 10.1111/j.1349-7006.2012.02307.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CD20 expression in B‐cell lymphoma between newly diagnosed, untreated cases and those after rituximab treatment

Abstract: Few studies have statistically investigated reduced CD20 expression in B‐cell lymphoma after rituximab therapy and genomic mutation of CD20 associated with reduction. We examined CD20‐positive rate in follicular lymphoma (FL) and diffuse large B‐cell lymphoma (DLBCL) by flow cytometry (FCM) and immunohistochemical staining (IHS), comparing 138 cases after rituximab therapy with 360 initial, not yet treated cases. Sequence analysis of exons 3 to 8 of CD20 was performed on 22 cases with low CD20‐positive rate af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Aberrant down-modulation of CD20 protein expression in DLBCL after treatment with Rituximab has been observed in the clinical settings [33][34][35] . Our results showed that Rituximab-mediated downregulation of CD20 is at the protein levels because the levels of CD20 mRNA expression sustained after treatment with Rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant down-modulation of CD20 protein expression in DLBCL after treatment with Rituximab has been observed in the clinical settings [33][34][35] . Our results showed that Rituximab-mediated downregulation of CD20 is at the protein levels because the levels of CD20 mRNA expression sustained after treatment with Rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed tissue samples from 22 cases diagnosed as CD5‐positive follicular lymphoma (FL) from 2005 to 2011 and 62 cases diagnosed as FL without CD5 expression, termed control cases, in 2006 in the Department of Pathology, Kurume University. Control cases were included and described in a previous study . Fresh materials were used for flow cytometry (FCM).…”
Section: Methodsmentioning
confidence: 99%
“…Control cases were included and described in a previous study. 13 Fresh materials were used for flow cytometry (FCM). Paraffin-embedded tissues were used for diagnosis and immunohistochemical staining (IHS).…”
Section: Patientsmentioning
confidence: 99%
“…Mutation analysis was performed as previously described. 16 In brief, exons 4-8 of TP53 were amplified from genomic DNA using PCR. PCR primers used in this study were detailed in the previous study.…”
Section: Mutation Analysis For Tp53mentioning
confidence: 99%